Effect of plant growth promoting rhizobacteria (PGPR) in seed germination and root-shoot development of chickpea (Cicer arietinum L.) under different salinity condition - Hossain, Mohammad Mosharraf; Das, Keshob Chandra; Yesmin, Sabina; Shahriar, Syfullah (Research in Agriculture Livestock and Fisheries, 2016)
Plant growth promoting rhizobacteria (PGPR) are beneficial bacteria that colonize plant roots and enhance plant growth by a wide variety of mechanisms. Ten isolates of bacteria designated as SS01, SS02, SS03, SS04, SS05, SS06, SS07, SS08, SS09 and SS10 were successfully isolated and morphologically and biochemically characterized. Subsequently to investigate the effect of PGPR isolates on the growth of chickpea, a pot culture experiment was conducted in 2013 at National Institute Biotechnology, Bangladesh net house. Prior to seeds grown in plastic pots, seeds were treated with PGPR isolates and seedlings were harvested after 21 days of inoculation. All the isolates were gram negative in reaction, catalase positive, produced indole acetic acid (IAA) as well as performed phosphate solubilization, able to degrade cellulose and have the adaptability in wide range of temperature and showed positive growth pattern in medium. Most of isolates resulted in a significant increasing of shoot length, root length and dry matter production of shoot and root of chickpea seedlings. Application of PGPR isolates significantly improves the percentage of seed germination under saline conditions. The present study, therefore suggested that the use of PGPR isolates SS04, SS10 and SS08 as inoculants biofertilizers might be beneficial for chickpea cultivation in saline condition Res. Agric., Livest. Fish.3(1): 105-113, April 2016